KANYOUKU DALAM NOVEL SHIKISAI WO MOTANAI TAZAKI TSUKURU TO KARE NO JUNREI NO TOSHI KARYA HARUKI MURAKAMI - Dwiyanti, Febri Nur; Hermandra, Hermandra; Suri, Intan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Idioms or in Japanese called kanyouku are often used by Japanese natives in communicating both orally and in writing. Kanyouku can be divided according to their structures and meanings. This study aims to determine the classification of kanyouku in the novel Shikisai wo Motanai Tazaki Tsukuru to Kare no Junrei no Toshi by Haruki Murakami. The theory used in this study is the classification of kanyouku based on the structure of form according to Miharu (2002) and based on meaning according to Muneo (1992). This research is a qualitative descriptive study. From the analysis of 35 kanyouku data containing elements of the upper limbs, it was found 31 doushi kanyouku, 3 keiyoushi kanyouku, and 1 meishi kanyouku. Based on the meaning, kanyouku in this study can be divided into kanyouku which represents feelings, behavior, actions and conditions.Key Words: Kanyouku, Idioms, Classification, Shikisai wo Motanai Tazaki Tsukuru to Kare no Junrei no Toshi, Haruki Murakami